2014
DOI: 10.1371/journal.pone.0097474
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based Study Examining Hepatitis B Virus Infection and Immunization Rates in Northwest China

Abstract: Background and AimCurrent baseline data regarding the prevalence of hepatitis B virus (HBV) infections and the immune status in hyperendemic areas is necessary in evaluating the effectiveness of ongoing HBV prevention and control programs in northwest China. This study aims to determine the prevalence of chronic HBV infections, past exposure rates, and immune response profiles in Wuwei City, northwest China in 2010.MethodsCross-sectional household survey representative of the Wuwei City population. 28,579 part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 25 publications
1
35
3
Order By: Relevance
“…Since that time, several studies [8][9][10][11][12][13][14] 12 3.17% in Sichuan blood donors (2010-2011) 13 and 2.73% in Beijing (2013-2014). 14 The rates varied in different areas and at different time periods.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, several studies [8][9][10][11][12][13][14] 12 3.17% in Sichuan blood donors (2010-2011) 13 and 2.73% in Beijing (2013-2014). 14 The rates varied in different areas and at different time periods.…”
Section: Introductionmentioning
confidence: 99%
“…15,16 OR value of contact with household carrier for exposure to HBV infection is 1.8 in one study in China. 17 A community based study in Tamilnadu shows that OR of 1.4 associations with family history of HBV and HBsAg positivity. 6 Odds of being infected are more among males, is consistent with other studies.…”
Section: Risk Factormentioning
confidence: 99%
“…4,9 In spite of these national TBD rates, HBV TBD remains problematic in China, with differences between birth province and migration status. Based on a population study in northwest China, Ji et al (2014) found that the lack of hepatitis vaccination was one of the main risk factors for HBV infection in children aged 1 to 14 y. 10 The migration of children from one region to another has also been found to be associated with low TBD rates.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a population study in northwest China, Ji et al (2014) found that the lack of hepatitis vaccination was one of the main risk factors for HBV infection in children aged 1 to 14 y. 10 The migration of children from one region to another has also been found to be associated with low TBD rates. 11 Unfortunately, there are no national data about HBV vaccination rates for migrant children.…”
Section: Introductionmentioning
confidence: 99%